Becoming pro-Palestinian testimonies from the global solidarity movement - Sayigh, Rosemary 1935- (Bloomsbury collections, 2024)
"Representing activists from over 40 countries, this book brings together testimonials from people of different nationalities and professions who are 'pro-Palestinian', whether as scholars, film-makers, artists, musicians, activists, or NGO workers. Using what oral historians call the 'focused life history', renowned scholar, Rosemary Sayigh, invites her contributors to describe the experiences, events, motives and feelings that led them to support the Palestinian cause. The book is the first of its kind in Palestiniography and includes voices from countries across the world, including Austria, Bosnia, Brazil, Cameroon, Chile, India, Iran, Italy, Japan, Norway, South Africa, the US and Vietnam. A chapter is dedicated to each country and contributors are asked to reveal how they 'discovered' Palestine - given that Palestine is rarely mentioned in school textbooks or university courses - whether by travel, friendship, study, membership in a political party or book group. They are also asked to detail what specific forms their engagement has taken - ranging scholarly, creative, militant, or charitable - and what their hopes are for the international solidarity movement. Finally, each contributor reflects on if they feel a just and equitable solution can ever be achieved for Palestinians, and if they accept the label 'pro-Palestinian' or would rather define their relationship to the Palestinians in some other way. With testimonies from both high profile and grassroots activists, the book is a rich and personal selection that reflects the diversity, dynamism and global nature of the movement for Palestine"."